RISK FACTOR ANALYSIS OF INCOMPLETE BASIC IMMUNIZATION IN CHILDREN AGED 12-23 MONTHS IN EAST NUSA TENGGARA PROVINCE - Almeida, Denisca; Benyamin Bebengu, Yahya; Syahrul, Fariani; Hargono, Arief (Universitas Airlangga, 2024)
Introduction: Immunization is an effective effort to prevent some dangerous diseases in children. By providing complete basic immunization, it can reduce child mortality. East Nusa Tenggara province reached a low number of complete basic immunization coverage in 2016 (69.29%), increased in 2017 (72.2%), then decreased again in 2018 (51.72%).Aims: of this study is to analyze risk factors for incomplete immunization status in children aged 12-23 months in NTT province. Method. The method used is analytical observational with a cross-sectional design. The data used are secondary data of Basic Health Research 2018. The study population was household members who could be interviewed at the time of Basic Health Research 2018 in the NTT provincial census block area. Total sample was 674 households. The sampling technique used is two stage one phase stratified sampling. The independent variables include mother's age, father's age, mother's education level, father's education level, number of children, residence, AEFI, and ANC. The dependent variable is the incomplete basic immunization status. Results: In this study, it is known that the candidate in the regression test variables are father's age (p value= 0.005), mother's educational level (p value= 0.000), number of children (p value= 0.007), residence (p value= 0.000), and ANC (p value= 0.000). Conclusion: According to this study, most children under two years were not fully immunized (63.2%). And in this research, the candidate variables will then become a prediction model of incomplete immunization status in children 12-23 months in East Nusa Tenggara province.